Training on making learning videos using OBS studio - Rizana, Dani; Huda, Miftahul (Universitas Muhammadiyah Magelang, 2021)
The Covid-19 pandemic has changed many things. Likewise, the world of information technology is developing so rapidly. The lesson is, when these two conditions meet, it will have an impact on the acceleration of the process of adopting information technology in all lines of life, including the world of education. Like it or not, the teachers have to prepare materials and an online learning process. One of them is using the OBS Studio application. The implementation method of the service includes lectures, demonstrations, exercises / practices, mentoring, and questions and answers. The result of the training activity was an increase in participants' understanding of using OBS Studio to make communicative and easy videos so that they could support online lectures during the Covid-19 pandemic.